2010
DOI: 10.1177/1363459309347478
|View full text |Cite
|
Sign up to set email alerts
|

Quitting is not an option: An analysis of online diet talk between celiac disease patients

Abstract: This is an empirical study of the way in which celiac disease patients manage the risk of gluten intake in their everyday life.The article examines naturally occurring conversational data in order to study how patients cope interactionally with constantly being at risk in their day-to-day living. They reject quitting the diet as a valid option, and instead construct a 'diet world' in which dietary transgression is presented as an integrated part of everyday life. In this way, patients can manage occasional die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Notions of individuality are variously drawn upon by participants as a discursive device in order to account for their decision making regarding adherence to health advice. Furthermore, instances in data that might initially be construed as individual agency, such as the self-reference of "I quit" in Veen and te Molder's (2010) study, is not simply viewed as an instance of individual agency, rather their sequential analysis highlights how dietary compliance is attended to as a communal activity. Discursive research is in a good position to illustrate the point raised by WHO (2000) in relation to obesity, that dieting should be treated as a population based problem and not an individual responsibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notions of individuality are variously drawn upon by participants as a discursive device in order to account for their decision making regarding adherence to health advice. Furthermore, instances in data that might initially be construed as individual agency, such as the self-reference of "I quit" in Veen and te Molder's (2010) study, is not simply viewed as an instance of individual agency, rather their sequential analysis highlights how dietary compliance is attended to as a communal activity. Discursive research is in a good position to illustrate the point raised by WHO (2000) in relation to obesity, that dieting should be treated as a population based problem and not an individual responsibility.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of naturalistic talk such as online forums allow us to examine the way that patients' manage such practical issues associated with diets. For instance, Veen and te Molder (2010) examined how patients with Celiac disease manage the risk of gluten intake. Following one thread initiated by a member whose subject title was "I want to quit" they found that other members rejected this as an option.…”
Section: Compliance As a Collective Phenomenonmentioning
confidence: 99%
“…These studies have shown that narratives can be used to give advice in a mitigated way, to express support and highlight common ground, to criticize behavior of other participants or to warrant previously made claims (e.g. Armstrong et al 2011;Harrison and Barlow 2009;Kouper 2010;Page 2012;Richardson 2003;Rudolf von Rohr 2015;Sillence 2010;Veen et al 2010). Several studies have indicated how narratives can be used to construct identities, for example as experts, novices, or communities.…”
Section: Theoretical Backdrop: Narratives and Identity Construction Imentioning
confidence: 99%
“…Similarly to Sequence 1, by drawing on his own experience and knowledge R2 provides support and so constructs a second story (Veen et al, 2010). That is, the alignment of a second response to the original response (Sacks, 1992).…”
Section: R2mentioning
confidence: 99%
“…By drawing on their own knowledge they are able to provide support for this novice; they are constructing second stories where the response is aligned to the original post (Veen et al, 2010;Sacks, 1992). Second stories work to normalise group views by displaying an understanding and stance towards the initial story (Arminen, 2004).…”
Section: R4mentioning
confidence: 99%